2018
DOI: 10.1097/md.0000000000011929
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of diffusion-weighted magnetic resonance imaging for local and skull base recurrence of nasopharyngeal carcinoma after radiotherapy

Abstract: Tumor recurrence is a major cause of nasopharyngeal carcinoma (NPC) treatment failure. Diffusion-weighted imaging (DWI) is used for a variety of cancers, but few data are available for NPC.The aim of the study was to investigate the DWI features of recurrent NPC after radiotherapy and apparent diffusion coefficient (ADC) thresholds for the diagnosis of recurrent NPC.This was a retrospective study of 160 patients with NPC treated by radiotherapy at the Cancer Hospital affiliated to Guangxi Medical University fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Most cancer lesions, including head and neck tumors, have a greater water diffusion restriction than normal tissues and benign structures, resulting in higher signal intensity on high-b-value images and lower signal intensity on ADC maps. Thus far, ADCs have been reported to differentiate among benign and malignant head and neck tumors, 18,19 lymph node metastases, and benign lymph nodes, [20][21][22] to determine and predict the response to treatment of head and neck cancer [23][24][25] and to differentiate between recurrence and posttreatment changes, [5][6][7][8][9][10][11][12][13][14] the main focus of this study. CT, MR imaging, and [ 18 F] FDG-PET/CT are the main diagnostic imaging modalities used during follow-up after treatment of head and neck cancer, primarily to detect recurrent lesions and differentiate them from posttreatment changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cancer lesions, including head and neck tumors, have a greater water diffusion restriction than normal tissues and benign structures, resulting in higher signal intensity on high-b-value images and lower signal intensity on ADC maps. Thus far, ADCs have been reported to differentiate among benign and malignant head and neck tumors, 18,19 lymph node metastases, and benign lymph nodes, [20][21][22] to determine and predict the response to treatment of head and neck cancer [23][24][25] and to differentiate between recurrence and posttreatment changes, [5][6][7][8][9][10][11][12][13][14] the main focus of this study. CT, MR imaging, and [ 18 F] FDG-PET/CT are the main diagnostic imaging modalities used during follow-up after treatment of head and neck cancer, primarily to detect recurrent lesions and differentiate them from posttreatment changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the ADC values of recurrent head and neck cancer lesions are lower than those of posttreatment changes. [5][6][7][8][9][10][11][12][13][14] However, due to the small sample size of most previously published series, the utility of ADC to differentiate recurrent lesions from posttreatment changes after treatment of head and neck cancer has not been definitively summarized and established. Therefore, this systematic review and meta-analysis aimed to summarize the existing data and evaluate the utility of ADC in this application.…”
mentioning
confidence: 99%
“…These findings suggest that DWI may be a more effective tool for detecting local recurrence and diagnosing clivus recurrent NPC in patients compared to routine MRI. (Wang C, Liu L, Lai S, Su D, Liu Y, Jin G, Zhu X & Luo N., 2018) In addition to its high diagnostic accuracy, DWI can also provide information on the extent and location of the tumor, as well as the involvement of nearby structures. This information is critical for treatment planning, as it can help determine the optimal treatment strategy and guide the selection of the appropriate treatment modality.…”
Section: Role Of Diffusion-weighted Imaging In the Diagnosis Of Nasop...mentioning
confidence: 99%
“…However, CT and PET-CT are radioactive, and do not clearly display the anatomical structure of the skull base, while MRI has the advantages of no radiation and high resolution of skull base anatomy, which makes radiation-free MRI the more favorable option [6]. With the continuous and rapid development of MRI technology, various MRI functional sequences have gradually matured, most notably conventional MRI, dynamic contrast-enhanced MRI (DCE-MRI), traditional diffusion-weighted imaging (DWI), and intravoxel incoherent motion DWI (IVIM-DWI) [7][8][9]. Some studies have applied DCE-MRI to the diagnosis of NPC, but DEC-MRI requires a contrast agent, which has limitations for patients with a history of allergies [10].…”
Section: Introductionmentioning
confidence: 99%